Pervasive gender bias in editorial boards of biodiversity conservation journals. (November 2020) - Liévano-Latorre, Luisa F.; da Silva, Rafaela Aparecida; Vieira, Raísa R.S.; Resende, Fernando M.; Ribeiro, Bruno R.; Borges, Fábio J.A.; Sales, Lilian; Loyola, Rafael
Abstract: Women are underrepresented in professional spaces, particularly at leadership positions. In science, the participation in editorial boards of journals is evidence of a high reputation within a specialty or field. Therefore, female presence in editorial boards can be used as a proxy for female presence and leadership in academic spaces. Here, we assessed the gender composition in editorial boards of 31 biodiversity conservation (BC) journals included in the Web of Science and obtained information on current and past editorial boards of these journals. We found pervasive gender bias in the editorial boards of the main scientific BC journals. Current editorial boards were composed of 1251 editors, of which only 28.7% were women. Nevertheless, gender biases are becoming smaller over time. Our projections indicate that BC journals may achieve gender balance in their editorial boards by the year 2038. We argue that a diverse and inclusive editorial board has greater chances to propose innovative solutions to conservation problems . Thus, the academic community, editors and journals must take proactive measures to achieve gender balance. Given that most editors are men, hiring women still depends on them; and these men need urgently to take their share of responsibility and be actors of change. More broadly, journals and science decision-makers must commit to their importance in the movement and start, for example, to hire and support women's work.